Identifikasi dan Analisis Forensik Rhodamin B dalam Lipstik yang Beredar di Pasaran Bandar Lampung dengan Metode Kromatografi Lapis Tipis (KLT) - Leni Simarmata; Saddam Husein; Candra Saka Nusantari (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Lipstick is a cosmetic product used to color the lips, providing a decorative effect and enhancing lip appearance. This study aims to identify the presence of Rhodamine B in lipstick samples using the Thin Layer Chromatography (TLC) method. The analysis was carried out by comparing the retention factor (Rf) values of the lipstick samples with the Rhodamine B standard. The samples consisted of ten red lipstick products coded A–J in stick form. Sampling was conducted using purposive sampling in Bandar Lampung markets, specifically Bambu Kuning Market and Central Market. The TLC method used silica gel GF 254 as the stationary phase and a mobile phase consisting of n-butanol, ethyl acetate, and ammonia (10:4:5) with a total volume of 25 mL. Detection was performed under UV light at 365 nm, which showed yellow fluorescence in samples D, E, H, and J. The Rf value of Rhodamine B standard was 0.85, while the Rf values of samples D, E, H, and J were 0.72, 0.78, 0.98, and 0.84, respectively. Samples were considered positive for Rhodamine B if the difference between the sample Rf value and the standard was less than 0.2. Based on these results, samples D, E, H, and J were identified as positive for Rhodamine B.